Attribute-based alterable threshold ring signature scheme with conspiracy attack immunity - Zhen CHEN; Wen-fang ZHANG; Xiao-min WANG (Tongxin xuebao)
Attribute-based cryptography is a generalization and development of the identity-based cryptography,which extends the identity to a set of attributes.In the attribute-based cryptosystem,different members with the same attributes can form a signature ring automatically,with the actual signer’s personl idnetity easily hided.By in-depth analysis of several attribute-based threshold ring signature schemes proposed by the earlier reseachers,it is concluded that the malicious users with the complementary attributes can conspire to forge a valid signature.In order to compensate for the defect,the proposal first gives the formal definitions of the security characteristics in attribute-based threshold ring signature scheme,such as unforgeability,indistinguishability and anti-collusion attack.Then a new attribute-based alterable threshold ring signature scheme is presented,whose security is proven equivalent to the computational Diffie-Hellman problem.By introducing an random secret parameter in each user’s private key,the proposal can resist the collusion attacks.It is proven that the proposal can satisfy existential unforgeability and anti-collusion against the adaptive chosen message attack in therandom oracle model,and can meet the requirement of indistinguishability among the users with the same attributes.Besides,property analysis shows that the proposal has high efficiency.